The role of FFR in clinical decision making in patients with moderate coronary lesions: a pilot study - Safi, Morteza; Mehrabi, Mohammad Ali; Alipour Parsa, Saeed; Khaheshi, Isa; Naderian, Mohammadreza (Acta Biomedica Atenei Parmensis, 2018)
Background and Aim: Applying fractional flow reserve (FFR) recently helped to assess borderline coronary defects and also facilitates assessment of these lesions. The present study aimed to assess cost-effectiveness of FFR in detection of these borderline lesions. Methods: This cross-sectional study was conducted on140 consecutive patients with 219 diseased arteries who underwent coronary angiography and suffered intermediate coronary lesions. Results: Of 18 patients who candidate for CABG before FFR, only one patient underwent CABG after determining FFR (P-value